Effect of exogenous salicylic acid under irrigation withholding at different growth stages in wheat (Triticum aestivum L.) - Dabzad, MA; Moghadam, HRT; Zahedi, H (International Journal of Natural Sciences, 2016)
Salicylic acid (SA), an endogenous plant growth regulator has been found to generate a wide range of metabolic and physiological responses in plants affecting their growth and development. In order to study effect of salicylic acid foliar application and limited irrigation on quantitative and qualitative characteristics of wheat, this experiment was conducted at Varamin, Iran during 2014 growing season. The experimental design was laid out in a randomized complete block with a split plots arrangement of treatments in three replications. Main plots included four different levels of irrigation (complete irrigation, irrigation withholding at stem elongation stage, irrigation withholding at flowering stage and irrigation withholding at seed filling period stage) and different concentration of foliar application of salicylic acid (0, 150 and 300 ?M) were allocated to subplots. The results showed that irrigation withholding conditions in different growth stages significantly decreased seed yield, RWC and total chlorophyll but by contrast increased membrane stability, proline content, SOD and CAT enzymes activity and also lipid and protein peroxidation. Salicylic acid foliar application had positive effect on all attributes in this experiment. In general, the results of the present study indicate that usage of salicylic acid reduces the harmful effects of water deficit stress and increases resistance to drought stress in wheat plant. International Journal of Natural Sciences (2014), 4(2) 28-33